Virus Variation Resource – improved response to emergent viral outbreaks - Hatcher, Eneida L.; Zhdanov, Sergey A.; Bao, Yiming; Blinkova, Olga; Nawrocki, Eric P.; Ostapchuck, Yuri; Schäffer, Alejandro A.; Brister, J. Rodney (Nucleic acids research, 2017)
The Virus Variation Resource is a value-added viral sequence data resource hosted by the National Center for Biotechnology Information. The resource is located at http://www.ncbi.nlm.nih.gov/genome/viruses/variation/ and includes modules for seven viral groups: influenza virus, Dengue virus, West Nile virus, Ebolavirus, MERS coronavirus, Rotavirus A and Zika virus Each module is supported by pipelines that scan newly released GenBank records, annotate genes and proteins and parse sample descriptors and then map them to controlled vocabulary. These processes in turn support a purpose-built search interface where users can select sequences based on standardized gene, protein and metadata terms. Once sequences are selected, a suite of tools for downloading data, multi-sequence alignment and tree building supports a variety of user directed activities. This manuscript describes a series of features and functionalities recently added to the Virus Variation Resource.